PENGARUH PENGGUNAAN METODE PEMBELAJARAN PROBLEM SOLVING TERHADAP HASIL BELAJAR MATERI POKOK MENENTUKAN UNSUR FISIK PUISI “TERATAI KEPADA KI HAJAR DEWANTARA” KARYA SANUSI PANE SISWA KELAS X SMA NEGERI-1 BARUS - Fatwa Alama (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2016)
his study aimed to examine the influence applying problem solvinglearning method to the learning ountcomes the subject matter determination thephysical elements of poem “The Lily to Ki Hajar Dewantara” by Sanusi Pane atgrade class X SMA Negeri 1 Barus. This research was conducted using thedescriptive and experiment method. The study population was all eighth gradestudents of SMP Negeri 1 Barus consisting of 4 classes totaling 160 student. Thesampling technique used is random sampling technique that is 25% of the totalpopulation. So that the samples are 40 students. For signaling hypothesis upheld inthis study received or rejected, the second is how inferential statistics using theformula test "t-test". From the calculations, t-count = 7,088, when compared with thevalue of t-table at the level of 95% confidence level or error rate of 5% with degrees offreedom (df) = (N - nr) = 40 - 2 = 38, the obtained t-table = 1,686. From the researchconducted it turns out the alternative hypothesis (Ha) that set acceptable, visiblefrom t-count is greater than t-table (7,088 > 1,686). Means that the hypothesis is upheldin this study can be accepted and approved. It means that there is significantinfluence applying problem solving learning method to the learning ountcomes thesubject matter determination the physical elements of poem “The Lily to Ki HajarDewantara” by Sanusi Pane at grade class X SMA Negeri 1 Barus.